Secondary teachers’ perception on the effectiveness of google classroom as a learning medium during movement control order / Raz Azira Md Ramly and Zulkifli Abd. Latiff - Md Ramly, Raz Azira; Abd. Latiff, Zulkifli (Centre For Media And Information Warfare Studies, 2021)
Technology has played vital role in all levels of education especially during the Movement Control Order (MCO) where people are confined to their homes along with the closure of schools, universities, and other educational institution. Generally, educators have turned to online teaching to ensure lessons are still going on. Google Classroom is one of the instruments that is free of charge and has earned recognition within a short period of time. However, online learning can be isolating and disengaging for learners. Sitting in front of a computer screen for hours may prompt a student to leave out a lesson altogether along with other issues that needs to be considered. The main purpose of the study is to explore the effectiveness of Google Classroom during the pandemic of COVID-19 phase from the perspective of secondary school teachers in Malaysia. The objective of the study is to identify teachers’ perceptions of effectiveness of Google Classroom and to identify the areas that can improve the effectiveness of Google Classroom as a learning medium. The research is conducted using a qualitative research design. The findings unveiled that secondary school teachers were neutral as they deem it as a minor part of their overall teaching approach. The evaluation of the discussions disclosed that Google Classroom has not produced a significant effect on the whole classroom teaching. The most important part that needs to be improved is the availability of Internet and gadgets as it is the core component needed to operate Google Classroom.